SOCIAL ADAPTATION OF JUVENILE PRISONERS IN THE POST-PRISON PERIOD: THEORY AND PRACTICE - Artyom Y. Nesterov (Scientific Journal of Pedagogy and Economics, 2019)
The article has developed mechanisms for post-prison adaptation of juvenile offenders. The problems of successful post-prison adaptation of a minor released were identified.